Pemberdayaan Usaha Terasi Tradisional Melalui Optimalisasi Produksi dan Strategi Pemasaran Digital di Desa Beringin, Deli Serdang - Sriani Sriani; Raja Nasrullah Fajrillah; Ouren Avellyola; M Abiyyu Wadi; Said Agil Lubs (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
Indonesia, as a maritime country with an area of approximately 3,544 million km2 or 75% of the total area of the Republic of Indonesia (RI) with the second longest coastline in the world, has abundant marine resources, one of which is shrimp that can be processed into shrimp paste. Shrimp paste, a traditional fermented product with high economic value, is still managed in a simple manner by business operators, such as Mrs. Eva's family business in Beringin Village, which has been operating since 2000 with a production capacity of 35 kg per period, increasing to 70 kg during Eid al-Fitr. This community service activity aims to increase production capacity and expand the marketing of shrimp paste businesses through the application of simple production strategies and digital marketing. The results show that the business faces problems of limited raw materials, manual processes, price fluctuations, and marketing that is limited to the local market without branding or digitalization. However, the business has a high profit margin and a distinctive taste that is a competitive advantage. Empowering businesses through production optimization and digital marketing strategies has proven to be able to improve product quality, strengthen business identity, and expand market access. Digitalization and simple innovations effectively boost the competitiveness of SMEs based on local wisdom. Recommendations include diversifying raw materials, standardizing production, providing ongoing training in branding and digital marketing, and fostering multi stakeholder collaboration to expand impact and ensure business sustainability.